Difficulties and Suggestions to Solve the Problem of Artistic Murals Subject for Students of the Department of Art Education - ئەوڕەحمان, د . دارا ئەوڕەحمان ئەحمەد (Sulaimani Journal for Humanities, 2025)
The aim of this research is to: 1- Identify the difficulties of the subject of artistic murals among students of the Department of Art Education. 2- Monitor proposals to solve the difficulties from the students' point of view. The descriptive approach was used to complete the research, according to the research topic and its objective, and the research sample consisted of students of the Department of Art Education in the fourth stage / morning classes in the art murals subject, then the researcher identified the obstacles and found a solid solution for them due to the scientific steps. The researcher prepared the scale according to the approved scientific steps, and it consisted of (6) main paragraphs and (16) secondary paragraphs. After extracting its apparent validity and stability by re-applying the scores at two different times, using the (Pearson) correlation equation, which has a value between (0.20-0.50). After applying it to the research sample, through statistical procedures, the research results were obtained and the weighted average for all paragraphs was (1.91), the level is low. In the light of this result, there are difficulties in the subject of artistic murals. In order to overcome the difficulties, a number of proposals were presented to solve the problem of the subject of artistic murals among students of the Department of Art Education. The study is ended with some proposals and recommendations.
Keywords: Difficulties; proposals; solution; problem; subject; artistic murals; students and art education